In Vitro Time Dependent Nicotine-Induced Free Radical Generation and Status of Glutathione Cycle in Murine Peritoneal Macrophage - Santanu Kar Mahapatra; Subhankari Prasad Chakraborty; Somenath Roy (Al Ameen Medical College, 2010)
: Nicotine is an alkaloid and the precursor to many tobacco carcinogens present in various tobacco products. The aim of the present study was to evaluate the free radical generation and status of the glutathione cycle in murine peritoneal macrophage during in vitro nicotine exposure with different time interval. Peritoneal macrophages were treated with 10mM nicotine in vitro for different time interval (3, 6, 9, 12, 15, 18, & 24h) and super oxide anion generation and components of glutathione cycle were analyzed. Super oxide anion generation, and NADPH oxidase activity got peak at 12hr, indicates maximum free radical generation through activation of NADPH oxidase in murine peritoneal macrophages during nicotine treatment. Reduced glutathione level, glutathione peroxidase, glutathione reductase, and glutathione-S-transferase activity were decreased significantly (p<0.05) with increasing time of nicotine treatment. But the oxidized glutathione level was time dependently increased significantly (p<0.05) in murine peritoneal macrophages. The redox ratio also decreased significantly (p<0.05) at all time of nicotine treatment. All the changes in peritoneal macrophages after 12hr in vitro nicotine treatment had no significant difference. From this study, it may be summarized that nicotine not only generates excess free radical but also affect the glutathione cycle in murine peritoneal macrophage.